2019
DOI: 10.3389/fpsyg.2019.00290
|View full text |Cite
|
Sign up to set email alerts
|

Group Metacognitive Therapy for Generalized Anxiety Disorder: A Pilot Feasibility Trial

Abstract: Background: Individual metacognitive therapy (MCT) for generalized anxiety disorder (GAD) is well established, but only one study has investigated the effectiveness of Group MCT (g-MCT) for GAD. The aim of the current study was therefore to evaluate the feasibility and effectiveness of g-MCT for GAD within a community mental health setting whilst addressing limitations evident in the previous study. Methods: The study used an open trial design, and 23 consecutively referred a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…MCT has also shown promising results when delivered using a group format in mental health settings. To date there have been nine studies evaluating Group-MCT across various disorders including obsessive compulsive disorder ( 20 , 21 ), generalized anxiety disorder ( 22 24 ), depression ( 25 , 26 ), and in mixed disorder groups ( 27 , 28 ). No studies to date have compared Group-MCT with individual MCT, but a preliminary comparison of Group-MCT with group mindfulness based stress reduction in mixed anxiety and depression groups found that both were feasible and acceptable, with large within-subject effects ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…MCT has also shown promising results when delivered using a group format in mental health settings. To date there have been nine studies evaluating Group-MCT across various disorders including obsessive compulsive disorder ( 20 , 21 ), generalized anxiety disorder ( 22 24 ), depression ( 25 , 26 ), and in mixed disorder groups ( 27 , 28 ). No studies to date have compared Group-MCT with individual MCT, but a preliminary comparison of Group-MCT with group mindfulness based stress reduction in mixed anxiety and depression groups found that both were feasible and acceptable, with large within-subject effects ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, even though change in anxiety accounted for independent variance in change in trait‐worry, change in negative metacognitive beliefs accounted for substantial more variance, which is in line with the metacognitive model of GAD (Wells, 1995) and a previous prospective study (Thielsch et al, 2015). Large improvements in trait‐worry in patients with GAD after Metacognitive therapy where metacognitions are modified have also been reported (Haseth et al, 2019; Normann & Morina, 2018).…”
Section: Discussionmentioning
confidence: 89%
“…MCT is a recommended treatment for GAD according to the National Institute for Health and Clinical Excellence guidelines (National Institute for Health and Clinical Excellence, 2011), and several studies have shown it to be an effective treatment for GAD, both in terms of short‐term (Nordahl et al, 2018; Normann & Morina, 2018; Wells & King, 2006) and long‐term results (Solem et al, 2021). Fewer studies have examined group‐based MCT, but there is evidence that group‐based MCT is also an effective treatment for GAD (Haseth et al, 2019; Van der Heiden et al, 2013). Most of the existing literature regarding MCT treatment for GAD is based on outcome studies, and there are fewer qualitative pragmatic studies describing the treatment.…”
Section: Introductionmentioning
confidence: 99%